The politically incorrect guide to American history - Woods, Thomas E., Jr., 1972- (Washington, D.C. : Regnery Pub. ; Lanham, Md. : Distributed by National Book Network, 2004)
Looks at American history with an irreverant and hard-hitting look at the nation's important people and events, concluding that the American Revolution was fought by conservatives and the First Amendment accepted state-sponsored churches.
The colonial origins of American liberty -- America's conservative revolution -- The Constitution -- American government and the "principles of '98" -- The North-South division -- The War Against the States -- Reconstruction -- How big business made Americans better off -- World War I -- The misunderstood Twenties -- The Great Depression and the New Deal -- Yes, Communist sympathizers really existed -- The approach of World War II -- World War II : consequences and aftermath -- Civil rights -- JFK and LBJ -- The decade of greed? -- Clinton -- Appendix : what really makes wages rise?
Includes bibliographical references and index.
Keywords: Political correctness -- United States